Automating the Integration of Viral Genomic Data: A Hierarchical Multi-Layered Approach for De-duplicating GenBank and GISAID Repositories - Alencar, Andrêza Leite de; Moraes, Laise de; Khouri, Ricardo (Anais Estendidos do Simpósio Brasileiro de Computação Aplicada à Saúde (SBCAS), 2026)
The rapid expansion of viral genomic sequencing has led to data fragmentation across major repositories like GenBank and GISAID. The same isolate could be deposited in both databases without any cross-reference linking the two entries. Consequently, there is no systematic way to identify this redundancy, which compromises the compilation of representative, non redundant large scale datasets. For Neglected Tropical Diseases (NTDs), this redundancy complicates real time genomic surveillance. This paper presents a computational framework designed to de-duplicate and integrate these databases using a hierarchical strategy: sequence identity, fuzzy string matching of isolate identifiers, and metadata reconciliation. Our results demonstrate that the tool effectively identifies redundant records for CHIKV-ECSA lineage and filters out laboratory derived sequences, providing a high-quality dataset for phylogeographic analysis.